2021
DOI: 10.1038/s41418-021-00813-z
|View full text |Cite
|
Sign up to set email alerts
|

MYH9-dependent polarization of ATG9B promotes colorectal cancer metastasis by accelerating focal adhesion assembly

Abstract: Tumour metastasis is a major reason accounting for the poor prognosis of colorectal cancer (CRC), and the discovery of targets in the primary tumours that can predict the risk of CRC metastasis is now urgently needed. In this study, we identified autophagy-related protein 9B (ATG9B) as a key potential target gene for CRC metastasis. High expression of ATG9B in tumour significantly increased the risk of metastasis and poor prognosis of CRC. Mechanistically, we further find that ATG9B promoted CRC invasion mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Previously, MYH9 has been reported to inhibit cell invasion, presuming (through the modulation of TP53 nuclear retention) to affect p53-responsive genes [ 36 ]. In this study, we demonstrated that MYH9 facilitates cell invasion in HNC ( Figure 1 ), and it has been shown in other cancers as well [ 16 , 17 , 18 , 19 , 20 , 21 ]. Several cellular mechanisms may be involved, including the modulation of epithelial-mesenchymal transition [ 18 , 19 ], focal adhesion assembly [ 20 ], and extracellular matrix ( Figure 1 D).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previously, MYH9 has been reported to inhibit cell invasion, presuming (through the modulation of TP53 nuclear retention) to affect p53-responsive genes [ 36 ]. In this study, we demonstrated that MYH9 facilitates cell invasion in HNC ( Figure 1 ), and it has been shown in other cancers as well [ 16 , 17 , 18 , 19 , 20 , 21 ]. Several cellular mechanisms may be involved, including the modulation of epithelial-mesenchymal transition [ 18 , 19 ], focal adhesion assembly [ 20 ], and extracellular matrix ( Figure 1 D).…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we demonstrated that MYH9 facilitates cell invasion in HNC ( Figure 1 ), and it has been shown in other cancers as well [ 16 , 17 , 18 , 19 , 20 , 21 ]. Several cellular mechanisms may be involved, including the modulation of epithelial-mesenchymal transition [ 18 , 19 ], focal adhesion assembly [ 20 ], and extracellular matrix ( Figure 1 D). Recent reports of MYH9 in other malignant functions have expanded the significance of this molecule.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Integrin α5 can regulate migration and invasion through the FAK/STAT3/AKT axis, and it also contributes to cell resistance to chemotherapy-related treatment [149]. Moreover, multiple molecules can be observed to regulate cells by crosstalk integrin-related signaling, such as Myosin Heavy Chain 9 (MYH9), Rab11, and Wnt5a [150][151][152], especially the latter, as the paracrine factors involved in EMT/MET have been found to modulate the ITGAV level in ovarian cancer [152]. Interestingly, the interaction of osteopontin and integrin αvβ3 can accelerate cellular uptake of glucose to improve cell migration ability [153].…”
Section: Cytoskeleton Remodelingmentioning
confidence: 99%
“…CRC has a good prognosis if it can be detected earlier and treated surgically (Li et al 2021). If the disease is already at an advanced stage, it can be treated with surgery, but the postoperative complications are also very frightening and directly related to the mortality of CRC (Bonney et al 2021;Henderson et al 2021;Kok et al 2021;Zhong et al 2021). However, the molecular mechanism of CRC in the pathogenesis was not clear.…”
Section: Introductionmentioning
confidence: 99%